Fathers’ feeding practices and children’s weight status in Mexican American families - Penilla, Carlos (Appetite, 2017)
Mothers’ feeding practices are associated with their children’s weight status, but little is known about the associations between fathers’ feeding practices and children’s weight status. Moreover, there is a dearth of research on Latino fathers’ feeding practices and children’s weight status, even though Latino children suffer some of the highest obesity rates in the U.S. We examined the associations between fathers’ feeding practices and child weight status, conditional on mothers’ feeding practices, within 174 Mexican American families with children aged 8–10 years. Parents completed the Parental Feeding Practices Questionnaire, which consists of four subscales: positive involvement in child eating, pressure to eat, use of food to control behavior, and restriction of amount of food. To assess child weight status, body mass index (BMI) was calculated and converted to age- and gender-specific percentile scores (BMI z-score). We fit four sets of regression models, one set for each of the four parental feeding practices subscales, with child BMI z-score as the outcome variable. Fathers’ pressure to eat (b = −0.20, p = 0.04; 95% CI: −0.39, −0.01) and use of food to control behavior (b = −0.36, p = 0.02; 95% CI: −0.65, −0.07) were associated with lower child BMI z-score, and restriction of amount of food (b = 0.56, p < 0.001; 95% CI: 0.27, 0.84) was associated with higher child BMI z-score, after accounting for mothers’ feeding practices. Fathers’ positive involvement in child eating was not associated with child BMI z-score. These findings provide empirical evidence that fathers’ feeding practices are independently associated with children’s weight status, even when mothers’ feeding practices are taken into account, and suggest that fathers’ feeding practices also matter in regard to children’s weight status.